Rancang Bangun Marketplace Dalam Mengembangkan UMKM Bidang Kuliner Di Kota Mataram Berbasis Android - Raynaldy Ramdhan Wardhana; Sri Endang Anjarwani; Nadiyasari Agitha (Informatics Engineering Dept., Faculty of Engineering, University of Mataram, 2023)
MSMEs (Micro, Small and Medium Enterprises) also contribute to Indonesia's economic growth. In running a business that is engaged in the MSME sector, there are many obstacles faced by most of the perpetrators, one of which is in terms of marketing. Based on research on MSMEs in the province of NTB, the number of MSMEs in Mataram City as of December 31, 2018 was 58,139 businesses. Although the government has made efforts to help MSME actors, there are still many MSMEs that are not yet known by the public so that sellers must promote their products in various places so that their products can be sold, one of which is by utilizing technology such as selling their products through applications. For this reason, in this study, the author builds an Android-based MSME marketplace application in the culinary field in the city of Mataram so that culinary MSME actors in the city of Mataram can promote and sell their products through the application. The process of making the application uses the SDLC (System Development Life Cycle) method with the waterfall model and testing with black box testing. In its design, the application is built using the Kotlin programming language and Firebase services. From testing after the application development process, the results from black box testing show that all test scenarios that have been made have been as expected. Furthermore, testing with MOS (Most Opinion Scrore) was also carried out and the results obtained were the average value of all respondents for a strongly agree score of 45.33%, agree at 34%, 16.67% for moderate, and 4.67% for disagree.